2014
DOI: 10.1073/pnas.1405628111
|View full text |Cite
|
Sign up to set email alerts
|

Simple chained guide trees give high-quality protein multiple sequence alignments

Abstract: Guide trees are used to decide the order of sequence alignment in the progressive multiple sequence alignment heuristic. These guide trees are often the limiting factor in making large alignments, and considerable effort has been expended over the years in making these quickly or accurately. In this article we show that, at least for protein families with large numbers of sequences that can be benchmarked with known structures, simple chained guide trees give the most accurate alignments. These also happen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
3
36
1
Order By: Relevance
“…For their overall difference, the P -values were estimated to be 0.016 for HomFam-TC and <0.01 for HomFam-SP, OXFam-SP and OXFam-TC by the Wilcoxon signed-rank test. Because this result is sharply inconsistent with the previous report (Boyce et al , 2014), we carefully inspected the cause of the difference. When MAFFT version 7.029 was used, as in their report, an improvement upon use of random chained guide trees was indeed observed.…”
Section: Resultscontrasting
confidence: 62%
See 4 more Smart Citations
“…For their overall difference, the P -values were estimated to be 0.016 for HomFam-TC and <0.01 for HomFam-SP, OXFam-SP and OXFam-TC by the Wilcoxon signed-rank test. Because this result is sharply inconsistent with the previous report (Boyce et al , 2014), we carefully inspected the cause of the difference. When MAFFT version 7.029 was used, as in their report, an improvement upon use of random chained guide trees was indeed observed.…”
Section: Resultscontrasting
confidence: 62%
“…The comparison between methods 1 and 2 was already reported in Boyce et al (2014) and Fox et al (2016), which consistently concluded that random chained guide trees (method 2) outperformed normal guide trees (method 1) for large alignments using various programs including MAFFT. The authors used MAFFT version 7.029, but the accuracy for large MSAs has been improved after this version.…”
Section: Methodsmentioning
confidence: 60%
See 3 more Smart Citations